Multimodal Interplay in the Puppet Show The Cricket and the Ant (Preučevanje otroške in mladinske književnosti, 2025)
The fable of the cricket and the ant is attributed to Aesop and has long since become a world cultural heritage, known in various literary forms and a wide variety of media adaptations. The puppet medium combines different modes of communication: linguistic (dialogues), sound (music as motif, music as background), visual and gestural (dramatic figures), spatial (figures, video). We present a micro-analysis of selected puppet performance regarding the communication modes and a macro-analysis, i.e. a summarised meaning of all the modalities of communication, their interconnectedness, and their messages. The show The Cricket and the Ant contains two types of connection between the source text and the performance: adaptation (Aesop’s fable); borrowing, by adding a dramatic character and changing the concept of understanding art as a work and not as a useless activity. The didactic starting points are based on the eighth key competence for lifelong learning – cultural awareness and expression.